Self-Identity Development among Indigenous Adolescents from the Far North of Russia - Natalia Flotskaya; Svetlana Bulanova; Maria Ponomareva; Nikolay Flotskiy; Tatiana Konopleva (Behavioral Sciences, 2019)
Self-identity is one of the fundamental needs of an individual. The most significant period of a person’s self-identity development is adolescence. The aim of this empirical study was to examine self-identity development among indigenous adolescents from the subarctic region of Russia. We identified specific features of personal identity among Nenets adolescents as compared to Russian adolescents. We also identified the dynamics of self-identity components among Nenets girls and boys during the transition period from the age of 12−13 to 14−15 years, and discovered characteristic features of self-identity among Nenets girls and boys.